2014
DOI: 10.1007/s10661-014-3881-8
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of pharmaceuticals in urban wastewater of north Indian cities and risk assessment

Abstract: Six pharmaceuticals of different categories, such as nonsteroidal anti-inflammatory drugs (ibuprofen, ketoprofen, naproxen, diclofenac), anti-epileptic (carbamazepine), and anti-microbial (trimethoprim), were investigated in wastewater of the urban areas of Ghaziabad and Lucknow, India. Samples were concentrated by solid phase extraction (SPE) and determined by high-performance liquid chromatography (HPLC) methods. The SPE-HPLC method was validated according to the International Conference on Harmonization gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(20 citation statements)
references
References 85 publications
0
19
0
1
Order By: Relevance
“…Carbamazepine, oxcarbazepine, and eslicarbazepine acetate, as structural relatives, can also be traced in the environment. Carbamazepine showed persistence after irradiation with sunlight (Matamoros et al, 2009) and has frequently been detected in the environment (Capdeville and Budzinski, 2011;Singh et al, 2014). For this reason, it has been used as an environmental tracer (Gasser et al, 2011).…”
Section: Usage Patterns Of Selected Active Pharmaceutical Ingredientsmentioning
confidence: 99%
“…Carbamazepine, oxcarbazepine, and eslicarbazepine acetate, as structural relatives, can also be traced in the environment. Carbamazepine showed persistence after irradiation with sunlight (Matamoros et al, 2009) and has frequently been detected in the environment (Capdeville and Budzinski, 2011;Singh et al, 2014). For this reason, it has been used as an environmental tracer (Gasser et al, 2011).…”
Section: Usage Patterns Of Selected Active Pharmaceutical Ingredientsmentioning
confidence: 99%
“…Thus, the 31 environmental emission of PPCPs can be expected to be high in Indian patients purchase medications without a prescription [36]. 48 Based on the measured concentrations in wastewater, an 49 estimated loading of antibiotics in a STP in India was reported 50 to range from 15.4 to 1395 g/day [36]. Inadvertent use of antibiotics 51 in India has led to an increase in the occurrence of drug resistant 52 microorganisms (i.e., superbugs) in the Indian environment [19].…”
Section: Introductionmentioning
confidence: 99%
“…The compounds were categorized based on the ecotoxicity data acquired by bioluminescence and respirometry assays and by predictions using the United States Environmental Protection Agency (US EPA) ecological structure-activity relationship (ECOSAR™). Singh et al (2014) al., 2014). It was confirmed that the WWTPs could not remove these antidepressants completely and the residual drugs in sewage effluents might pose an environmental hazard based on the determined risk quotients.…”
Section: Chemical Hazardsmentioning
confidence: 99%